The mechanistic role of active site residues in non-stereospecific haloacid dehalogenase E (DehE) using computational approach - Muhammad Hasanuddin bin Zainal Abidin (Kulliyyah of Science, International Islamic University Malaysia, 2019)
Dehalogenase E (DehE) is a non-stereospecific haloacid dehalogenase produced by soil bacteria, Rhizobium sp. RC1. This enzyme has been hypothesized to facilitate 'direct attack mechanism' using an activated water molecule for directly attacks the α-carbon of haloacid compound, thus releasing the halogen. The similar mechanism has been identified for Dehalogenase I (DehI) from Pseudomonas putida PP3 which belongs under the same group of DehE. For clarification on DehE catalytic mechanism, this enzyme was docked with D- and L- stereoisomer of 2-Chloropropionic acid (2CP) and their complex structures were simulated using GROMACS 5.1.2 for 50 nano-seconds. Upon completion, the distance of catalytic water towards Asn114, Asp189 and the α-carbon of the 2CP were precisely calculated. The same procedure was also applied to DehI as it serves as a benchmark. Result analysis of DehE simulation had revealed information on the presence of water molecule, potential of water activation and direct attack on substrate. In this study, the catalytic water was found located nearby Asn114 through hydrogen bonding. For water activation, the distance of Asp189 towards water molecule was found in the range of ~2.0 to ~8.0 Å. This aspartate residue was proposed to activate the catalytic water when these two molecules were in close contact. While for the direct attack, the distance of water molecule towards the α-carbon of 2CP was approximately ~4.0 Å provided that the molecular arrangement has taken place in active site. In conclusion, DehE is strongly suggested to facilitate 'direct attack mechanism' for haloacid catalysis. This study information will provide a platform for isotope labeling experiment for non-stereo haloacid dehalogenase especially for DehE.